Cost Of Cultivation And Marketing of Pepper In Cannanore District - Santhosh P (Department of Agricultural Economics, College of Horticulture, 1985)
The study was based mainly on the data collected from a sample of farmers and market intermediaries in Cannanore district of Kerala during the year 1982-’83. Data for estimating the cost of cultivation were generated from a random sample of 72 farmers, stratified on the basis of size holding. The costs were analysed input wise, operation wise and also based on ABC cost concepts in the aggregate level and stratum level. Capital productivity analysis was also attempted to study the economic feasibility of pepper cultivation. Pepper marketing was studied from the level of producers to the terminal market at Cochin. Price spread was worked out through the method of concurrent margins. Cost of production analysis was carried out both at the aggregate level and at the stratum levels for a period of seven years viz. from planting till the crop attained the stage of yield stabilisation. The annual cost for the seven year period at the aggregate level was found to be Rs.5,605, during the first year, Rs.2,475.06 in the second year, Rs.3,481.80 in the third year, Rs.3,514.48 in the fourth year, Rs.3,992.72 in the fifth year, Rs.4,715.12 in the sixth year and Rs.5,681.68 in the seventh year. In general the most conspicuous cost creating input was human labour while the corresponding operation was intercultural operations. Roughly one-fourth of the total cost was fixed cost and the rental value of the land was the predominant item in this. The cost of cultivation was highest in stratum II and less in stratum I. Analysis of capital productivity revealed that the investment on pepper cultivation had a pay back period of nine years two months and eleven days, benefit-cost ratio of 1.16, Net present worth of Rs. 6,646 and an internal rate of return of 17.22 per cent. The market practices, marketing costs, market structure and price spread were also studied. The marketing channels identified were: 1. Producer → Pre-harvest contractor → Wholesaler →Exporter 2. Producer → Village Merchant → Wholesaler → Exporter 3. Producer → Wholesaler → Exporter 4. Producer → Village Merchant → Commission agent → Wholesaler → Exporter 5. Producer → Commission agent → Wholesaler → Exporter 6. Producer → Village Merchant → Internal wholesaler (Consignment trade) The price spread in these six channels were worked out to be 28 per cent, 17.45 per cent, 12.65 per cent, 18.91 per cent, 14.11 per cent and 14.01 per cent respectively.